2012
DOI: 10.1038/ng.2434
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RNA lariat debranching enzyme suppresses TDP-43 toxicity in ALS disease models

Abstract: ALS is a devastating neurodegenerative disease primarily affecting motor neurons. Mutations in TDP-43 cause some forms of the disease, and cytoplasmic TDP-43 aggregates accumulate in degenerating neurons of most ALS patients. Thus, strategies aimed at targeting the toxicity of cytoplasmic TDP-43 aggregates may be effective. Here we report results from two genome-wide loss-of-function TDP-43 toxicity suppressor screens in yeast. The strongest suppressor of TDP-43 toxicity was deletion of Dbr1, which encodes RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
216
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(226 citation statements)
references
References 71 publications
(94 reference statements)
7
216
0
Order By: Relevance
“…A similar stable intron is derived from the murine cytomegalovirus (Kulesza and Shenk 2006). Finally, in a recent study it was shown that lariat introns accumulate in the cytoplasm of dbr1Δ yeast cells (Armakola et al 2012). Thus, there is precedence that lariats derived from introns can be found in the cytoplasm, where they are relatively stable.…”
Section: Discussion a Population Of Lariat Sisrnas In The Cytoplasmmentioning
confidence: 99%
“…A similar stable intron is derived from the murine cytomegalovirus (Kulesza and Shenk 2006). Finally, in a recent study it was shown that lariat introns accumulate in the cytoplasm of dbr1Δ yeast cells (Armakola et al 2012). Thus, there is precedence that lariats derived from introns can be found in the cytoplasm, where they are relatively stable.…”
Section: Discussion a Population Of Lariat Sisrnas In The Cytoplasmmentioning
confidence: 99%
“…Cells may need to efficiently degrade tRNA introns to generate nucleotides or prevent introns from interacting with other RNAs and RNA-binding proteins and perhaps inhibiting their functions. There is precedent for this, as cytoplasmic accumulation of mRNA intron lariats in human cells sequesters and suppresses TDP-43, a key factor involved in amyotrophic lateral sclerosis (Armakola et al 2012). …”
mentioning
confidence: 99%
“…Armakola et al [114] identified a novel protective strategy by conducting an unbiased screen for genetic modifiers of TDP43-based toxicity in yeast. One of the top hits from this screen was debranching enzyme 1, a protein required for the metabolism of intron lariats formed during RNA splicing.…”
Section: Rna Granulesmentioning
confidence: 99%
“…Deletion of the RNA-binding domain prevents the toxicity of cytoplasmic TDP43 and FUS [39][40][41], and dbr1 deficiency creates a similar effect by flooding cells with intron lariats that compete for TDP43's RNA binding sites [114]. A primary abnormality in nucleocytoplasmic transport would be expected to stimulate mislocalization of TDP43 and FUS, and, as a result, disrupt RNA processing.…”
Section: Alternative Rna-based Mechanismsmentioning
confidence: 99%